2014
DOI: 10.1007/s10439-014-1104-7
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on the Clinical Translation of Scaffolds for Tissue Engineering

Abstract: Scaffolds have been broadly applied within tissue engineering and regenerative medicine to regenerate, replace, or augment diseased or damaged tissue. For a scaffold to perform optimally, several design considerations must be addressed, with an eye toward the eventual form, function, and tissue site. The chemical and mechanical properties of the scaffold must be tuned to optimize the interaction with cells and surrounding tissues. For complex tissue engineering, mass transport limitations, vascularization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
149
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(149 citation statements)
references
References 116 publications
(118 reference statements)
0
149
0
Order By: Relevance
“…The cohort expressing both growth factors simultaneously was found to be better in terms of the formation and deposition of newly formed bone compared to the cohorts expressing only one of the two growth factors in rabbit orbital defect model [72]. The delivery of VEGF in combination with the osteogenic BMP-2 induces neo-vascularization of the newly formed bone tissue thus enabling superior supply of nutrients [73].…”
Section: Gene Delivery By Cells Ex Vivo Transfected With Bmp-2 Encodimentioning
confidence: 97%
“…The cohort expressing both growth factors simultaneously was found to be better in terms of the formation and deposition of newly formed bone compared to the cohorts expressing only one of the two growth factors in rabbit orbital defect model [72]. The delivery of VEGF in combination with the osteogenic BMP-2 induces neo-vascularization of the newly formed bone tissue thus enabling superior supply of nutrients [73].…”
Section: Gene Delivery By Cells Ex Vivo Transfected With Bmp-2 Encodimentioning
confidence: 97%
“…The efficacy of manual decellularisation has been demonstrated successfully by numerous groups, and manually prepared xenogenic-derived tissue substitutes have been used in clinical practice for many years; however, little attention has been directed towards their 'upscaled' production [Badylak, 1989;Price et al, 2014;G et al, 2015;Webber et al, 2015]. In this current ex vivo study, a comparative analysis of the repeatable nature of ADP, which was previously described for the preparation of ovine aortaderived ECMs, was investigated using Triton X-100 as the main active decellularisation reagent [Mooney et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…As decellularised extracellular matrices (ECMs) become more relevant in delivering these advanced tissue therapies, automation of the decellularisation process will ultimately be required to provide for the increasing number of patients and also at an affordable sustainable price for world health care providers [G et al, 2015]. Various authors such as G et al [2015] and Webber et al [2015] have suggested that one of the principal reasons that so little clinical translation has occurred to date is due to the extremely high costs of delivering such treatments and also the lack of availability of quality-assured consistent ECMderived scaffolds for implantation and research purposes Price et al, 2014;G et al, 2015;Webber et al, 2015]. They have suggested that 'up-scaled' production is one key area that needs greater investigation, to ensure cost-effectively decellularised ECM scaffolds which can safely be used to treat a much larger cohort of patients [WHO, 2013;G et al, 2015;Webber et al, 2015].…”
mentioning
confidence: 99%
See 2 more Smart Citations